Pengaruh Pengendalian Akuntansi, Pengendalian Perilaku, dan Pengendalian Personal terhadap Kinerja Manajerial, dengan Moderasi Karakteristik Tugas (Studi pada Kantor Akuntan Publik di Provinsi Jawa Tengah dan DIY) - P, Januar Eko; Kustianingsih, Erna (Akutansi Bisnis & Manajemen ( ABM ), 2007)
This study tests the influence of effectiveness of accounting, behavior and personnel forms of control by managerial performances with moderating task characteristics on Public Accountant. Respondents participating in the study are manager and submanager. The study uses survey method. The hypothesis was analyzed using Modereted Regression Analysis (MRA). The result show effectiveness of accounting, behavior and personnel forms of control influence with managerial performance. Personnel forms of control moderating task characteristics influence by managerial performance.